Mariátegui and the occidentalization of politics - Melgar Bao, Ricardo (FCL-UNESP Laboratório Editorial, 2007)
The contribution of Mariátequi for the view of socialism in Latin America is recovered not only through the criticism of the cultural and political marginal position of the non-western people but also through the particular way he used marxism, reinforcing its universal characteristics by the cultural appropriation of different cultural contexts.